Urinary Prothrombin Fragment 1+2 in relation to Development of Non-Symptomatic and Symptomatic Venous Thromboembolic Events following Total Knee Replacement. (28th March 2011) - Borris, Lars C.; Breindahl, Morten; Lassen, Michael R.; Pap, Ákos F.
Abstract : Prothrombin fragment 1+2 is excreted in urine (uF1+2) as a result of in vivo thrombin generation and can be a marker of coagulation status after an operative procedure. This study compared uF1+2 levels in patients with symptomatic and non-symptomatic venous thromboembolism (VTE) after total knee replacement (TKR) and in event-free sex- and age-matched controls. Significantly higher median uF1+2 levels were seen in the VTE patients on days 1, 3, and the day of venography (mostly day 7) after TKR compared with controls. The uF1+2 levels tended to be high in some patients with symptomatic VTE; however, the discriminatory efficacy of the test could not be evaluated. In conclusion, this study showed that patients with VTE tend to have significantly higher uF1+2 levels compared with patients without events between days 1 and 7 after TKR surgery. Measurement of uF1+2 could provide a simple, non-invasive clinical test to identify patients at risk of VTE.